2000
DOI: 10.1007/s004210050661
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal responses to high- and moderate-intensity strength exercise

Abstract: The hormonal responses of nine male, strength athletes to strength exercise were examined. The athletes performed one moderate- and one high-intensity strength exercise workout. In the high-intensity workout, the load was 100% of each subject's three-repetition maximum (3-RM) for squats and front squats, and 100% of each subject's six-repetition maximum (6-RM) for leg extensions. In the moderate-intensity workout, the load was 70% of the high-intensity protocol. Rest periods between sets were 4-6 min for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
3
18

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 29 publications
7
94
3
18
Order By: Relevance
“…Kraemer et al 1990;Häkkinen and Pakarinen 1993;Gotshalk et al 1997;Raastad et al 2000;Ratamess et al 2005). Furthermore, the finding of no change in hormonal levels during the A training, which included low muscle mass and low training volume, is also in line with previous findings (Häkkinen and Pakarinen 1993;Gotshalk et al 1997;Ratamess et al 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Kraemer et al 1990;Häkkinen and Pakarinen 1993;Gotshalk et al 1997;Raastad et al 2000;Ratamess et al 2005). Furthermore, the finding of no change in hormonal levels during the A training, which included low muscle mass and low training volume, is also in line with previous findings (Häkkinen and Pakarinen 1993;Gotshalk et al 1997;Ratamess et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…In the L+A sessions, the general warm-up was followed by two warm-up sets in leg press with gradually increasing load. The leg exercise protocol was based on prior studies showing that involvement of a large muscle mass, high in volume, moderate to high in intensity, using short rest intervals; tend to produce the greatest acute hormonal elevations (Raastad et al 2000;Smilios et al 2003;Kraemer and Ratamess 2005). Leg exercises performed were:…”
Section: Trainingmentioning
confidence: 99%
“…Many authors reported studies on repeated maximal exercises [1][2][3][4][5][6][9][10][11][12] consisting of 3 to 10 bouts separated by intermissions of constant or variable duration but offered no global assessment of a series of exercise bouts. The aim of this study was to assess the anaerobic endurance of untrained male and female subjects by applying the so-called performance index to repeated maximal exercises.…”
Section: Introductionmentioning
confidence: 99%
“…O TR, atividade voltada para o desenvolvimento das funções musculares através da aplicação de sobrecargas, é uma intervenção capaz de promover expressivos aumentos de força e massa muscular em idosos (7) . Os exercícios resistidos induzem respostas fisiológicas agudas importantes para ganhos de força e hipertrofia muscular; alterações hormonais que promovam um "ambiente" anabólico apresentam papel importante nas adaptações crônicas induzidas pelo treinamento (8) . Por outro lado, em indivíduos com idade avançada, essas respostas precisam ser mais bem caracterizadas.…”
Section: Introductionunclassified
“…O cortisol, principal glicocorticóide secretado pela ativação do eixo hipotálamo-hipófise-adrenal, apresenta função catabólica e parece sofrer elevação transitória após uma sessão de exercícios resistidos (11) . Em adendo, tem sido sugerido que a razão testosterona/cortisol (RTC) seja um indicador do status anabólico/catabólico do músculo esquelético durante o TR (12) e as respostas aos exercícios resistidos são dependentes, dentre outros fatores, da intensidade realizada (8) . O hormônio do crescimento (GH), secretado pela hipófise anterior, apresenta papel relevante na síntese protéica e por isso tem sido foco de estudos que versam sobre as respostas agudas aos exercícios resistidos (13)(14) .…”
Section: Introductionunclassified